PERAN DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, DAN KEPEMILIKAN INSTITUSIOAL TERHADAP PENGUNGKAPAN SUSTAINANBILITY REPORT - Lasdi, Lodovicus; Mulia, Teodora Winda; Petta, Catherine Cynthia Monica (Universitas Serang Raya, 2025)
Sustainability report is a report to disclose the company's performance in terms of social, environmental and community as a form of accountability to internal and external stakeholders to realize corporate sustainability. This study aims to test and analyze the effect of independent board of commissioners, audit committee and institutional ownership on sustainability report disclosure. The population of this study are non-financial and non-banking companies listed on the Indonesia Stock Exchange in 2019-2022. This type of research is quantitative data. The data collection technique used in this research is purposive sampling. With the research data used, namely documentation in the form of financial reports and sustainability reports on the IDX website and the website of each company. The analysis method used in this research is multiple linear regression analysis. Measuring the disclosure of sustainability reports in this study using GRI-G4 standard indicators in 2015-2016, which includes 91 disclosure items from the Global Reporting Initiative. The results of this study indicate that the audit committee has a positive effect on the disclosure of sustainability reports, while the independent board of commissioners and institutional ownership have no effect on the disclosure of sustainability reports. The conclusion of this study is that the audit committee plays an important role in the disclosure process of sustainability reports. This is because the audit committee's oversight of the disclosure of a sustainability report increases the transparency of management's presentation of a sustainability report in accordance with the principles of good corporate governance.